Impact of land use changes in Sungai Pulai mangrove on socioeconomy of the local community - Sarmin, Noor Shaila (2017)
The importance of mangrove ecosystem to the community and environment cannot be underestimated. Local community largely depends on this natural endowment for their subsistence and commercial activities. The mangroves in Sungai Pulai and its surrounding areas in Johor, Peninsular Malaysia were reduced due to anthropogenic pressures mainly for land use/covers (LUCs) changes for developments which affected the local mangrove-dependent communities (mainly fishermen) livelihood. The objective of the present study was to assess the spatiotemporal changes of LUCs in and around Sungai Pulai mangroves during 2004 to 2014 with possible anthropogenic causes of mangrove change and socioeconomic impacts to local community’s livelihood. The study integrated the application of remote sensing (RS) and geographic information system (GIS) with household survey data. Satellite RS data and GIS were used to assess LUCs changes during the study period. A cross-sectional household survey was conducted using a structured questionnaire with 360 respondents in order to identify local community’s present socioeconomic status and their perception on mangrove change issue, causes and impacts of mangrove change to their socioeconomics. For the change detection analysis, three multi-temporal Landsat imageries (Landsat 5 TM for 2004 and 2009, and Landsat 8 OLI-TIRS for 2014) were used. Supervised classification technique with maximum likelihood classifier (MLC) was employed to categorize the LUCs into five classes such as mangrove, other vegetation, oil palm, built up and water body. The accuracies of the mapping of the satellite imageries were 96.09% (2004), 96.83% (2009), and 98.52% (2014). Annual change rates for each LUCs type were also calculated. The finding showed that LUCs of the study area changed and built-up area was increased resulting reduction of mangroves or other LUCs. Annual build up area increasing rate was 905.39 ha/year (7.44%) and reduction rate of mangrove area was 114.17 ha/year (-1.14%), oil palm area was 370.90 ha/yr (-1.56%), other vegetation area was 409.02 ha/yr (-7.75%) and water body area was 11.53 ha/yr. At mukim level study, except Sungai Karang, all the mukims faced mangrove loss. In Malaysian perspective, though oil palm area has been increasing in recent days the change detection study found that oil palm coverage has been decreasing at the study area. Annually 155.06 ha, 27.69 ha, 468.56 ha, 117.68 ha, 112.99 ha and 23.33 ha of build up area increased in mukim Tanjung Kupang, Jelutong, Pulai, Jeram Batu, Serkat and Sungai Karang, respectively. Therefore, annually 20.81 ha, 1.58 ha, 34.12 ha, 18.52 ha and 46.65 ha of mangrove area were reduced in mukim Tanjung Kupang, Jelutong, Pulai, Jeram Batu and Serkat, respectively. Respondent’s perceived urban development as the major cause of mangrove change followed by overharvesting/clear logging, coastal erosion, policy & management, accessibility to market & national highways, population pressure, migrant population pressure, farm size expansion, poverty rate, higher income from non-mangrove source, water & oil pollution, education level, agriculture expansion and aquaculture expansion. From the correlation analysis, urban development, population growth, migrant population growth, policy & management, coastal erosion, water & oil pollution, overharvesting and aquaculture were significantly related to mangrove change. However, the perceptions differed by mukims as the LUCs, pressures and drivers were different. Different ongoing mega development projects opened job opportunities at different employment levels which resulted an increase of population and migrants in the study area. Mukim Pulai and Tanjung Kupang faced huge infrastructural developments which directly affected mangrove coverage. Mukim Serkat also faced a drastic mangrove loss which resulted from the combined effect of the mixed development, shoreline erosion and oil pollution from the ship harboring at the port. As negative impacts the respondents’ perceived species and habitat loss as the highest priority followed by increase of coastal erosion, mangrove production reduced, mangrove income reduced, biodiversity threatened, increased migrants and increased risk of livelihood. However, as positive impacts respondents perceived new infrastructures developed for useful purpose replacing mangroves as number one followed by improved communication system and increased the overall quality of living standards. The study concluded that the area under investigation was facing a rapid development during the study period and conversion of mangroves and other LUCs to built-up areas impacted the local communities’ livelihood both positively and negatively.